Land, Law, and Leniency: Unpacking the Effectiveness of Sanctions in Land-Related Crimes - Suci, Wahyu Wulan; Arifin, Ridwan (Law Research Review Quarterly, 2025)
Land disputes are increasingly prevalent in Indonesia, often resulting in significant harm to individuals and communities, particularly in cases of land grabbing. Land grabbing refers to the unlawful occupation or appropriation of land without the owner's consent, which may involve encroachment, falsification of land certificates, or alteration of land boundaries. Such acts constitute criminal offenses under Article 385 of the Indonesian Criminal Code (KUHP). However, enforcement remains weak, and judicial decisions frequently result in disproportionately lenient sentences. This raises serious concerns about the deterrent effect of penal sanctions and the broader implications for land governance. Factors contributing to land grabbing include ignorance or neglect of land ownership rights, speculative practices, and the increasing value of land. This research investigates the effectiveness of penal sanctions in land-related crimes, focusing on lenient sentencing patterns in Indonesian court decisions. Using a normative juridical approach combined with document analysis, this study analyzes Supreme Court decisions over the past decade to assess the extent of sentencing disparities and the lack of clear judicial guidelines. Findings reveal a consistent trend of light punishments that fail to reflect the gravity of the offenses or deter future violations, thereby exacerbating agrarian conflicts and undermining the rule of law. The urgency of this issue lies in the continued vulnerability of rightful landowners and the erosion of public confidence in the legal system. This study contributes to legal reform discourse by recommending the development of clearer sentencing guidelines and more equitable legal frameworks to ensure justice and prevent recurring land crimes in Indonesia.